Analysis of Hydroponic Green Lettuce Marketing Strategy at PT Amboja Global Lestari, Sleman Regency, Yogyakarta - Naufal Arrahman Surya; Darsono Darsono; Raden Kunto Adi (Journal of Global Sustainable Agriculture, 2023)
Vegetable business opportunities, one of which is green lettuce, is still quite high. PT Amboja Global Lestari is a producer of hydroponic-based green lettuce. There is competition from green lettuce producers in Yogyakarta province and surrounding areas which significantly affects the sales level of PT Amboja Global Lestari's hydroponic green lettuce, so it is necessary to plan a strategy to be able to win the competition. The purpose of this study is to identify internal and external factors of hydroponic green lettuce marketing, analyze alternative marketing strategies, and determine the priorities of hydroponic green lettuce marketing strategies. The basic method of research uses a descriptive method with a qualitative approach. The data analysis method uses IFE Matrix, EFE Matrix, IE Matrix, SWOT Matrix, QSPM. The results of data analysis show internal factors that are the company's main strength in marketing hydroponic green lettuce, namely, quality green lettuce products, good service to consumers, guaranteed product quality guarantees to consumers, and online and offline promotions and sales are running well, with the highest score of 0.31, while for the main weakness, the distance to the hydroponic garden is quite far with the lowest score of 0.09. The main external opportunities are high consumer demand for vegetables, and there are often exhibitions with a score of 0.35, while the main threats are, the increase in new competitors, effective competitor marketing online and offline, and disease and fungal attacks, with a score of 0.21. IE Matrix Analysis shows that the company is in a position to grow and develop. The SWOT Matrix Analysis resulted in six alternative marketing strategies. QSPM analysis resulted in the main strategy priority of hydroponic green lettuce marketing, namely, increasing the quality and quantity of hydroponic green lettuce with a total TAS value of 7,615.